Re-induction of desiccation tolerance in germinated cowpea seeds - Silva, A. C. da [UNESP]; Davide, L. C.; Braz, G. T.; Maia, J. [UNESP]; Castro, E. M. de; Silva, E. A. A. da [UNESP] (Elsevier B.V., 2017)
The objective of this work was to re-induce desiccation tolerance (DT) in cowpea germinated seeds and to investigate the mechanisms related to the re-induction of DT in this species. For this, germinated seeds with primary roots with length of 1, 2, 3 and 4 mm were treated with osmotic solution of polyethylene glycol 6000 (PEG) of - 1.7 MPa at 10 degrees C for 24, 48 and 72 h. Those seeds were dried, rehydrated and evaluated regarding the reinduction of DT. We studied mitosis events and performed scanning electron microscopy (SEM) in primary roots of untreated and PEG-treated germinated seeds. Furthermore, we quantified the glucose, sucrose and raffinose contents during the re-induction of DT. The re-induction of DT in cowpea germinated seeds with primary roots with length up to 2 mm was successfully obtained through an osmotic treatment of PEG during 24 h. The PEG treatment favored the maintenance of cellular structure integrity, the arrest of cell cycle and the accumulation of sucrose in the primary roots. Those mechanisms may contribute to re-induction DT in germinated cowpea seeds. (C) 2017 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Cell cycle; Cell ultrastructure; Non-reducing sugar; Osmotic treatment; Vigna unguiculata